QUALITATIVE EVALUATION OF THE IMPACT OF INTERNATIONAL COMPETITIVENESS FACTORS OF THE RUSSIAN REGIONS - A. V. Timiryasova; T. V. Kramin; M. V. Kramin (Russian Journal of Economics and Law)
Objective: to identify, classify and quantify the influence of key factors of international competitiveness on the Russian regions and to determine the main directions of its improvement. Methods: institutional and systemic approaches, factorial and comparative analysis, econometric modeling tools. Results and scientific novelty: basing on empirical data of the 30 most economically developed Russian regions, the econometric models are elaborated for quantitative evaluation of the factors of their international competitiveness. The basic directions of increasing the international competitiveness of Russian regions are revealed. Practical value: the basic directions of increasing the international competitiveness of the Russian regions are presented and substantiated: infrastructure development, business climate, regional institutional environment, and improving the quality of state management at regional level. They allow to elaborate a complex of practical measures for solvingthe above problem.